Hubungan Tingkat Kecemasan Belajar Dan Kemampuan Literasi Sains Dengan Hasil Belajar IPA Mahasiswa PGSD UNSAR - Purnama, Zulfah Rizka; Hermin, Hermin; Laely, Nur; Hamidah, Ida Sitti; Tukan, Kristina Ina Tuto (P3M Politeknik Negeri Ambon, 2023)
This research was carried out at Werisar University for the 2022/2023 academic year. The aim of this research is to determine (1) the relationship between learning anxiety and the science learning outcomes of PGSD students (2) the relationship between science literacy abilities and the science learning outcomes of PGSD students (3) analyzing the relationship between learning anxiety and science literacy abilities and the science learning outcomes of PGSD students. This type of research is comparative causal or ex post factor research which is correlational in nature. The research design used is a quantitative research design with two independent variables. Data sources were taken directly using instruments in the form of science learning anxiety questionnaires, scientific literacy ability tests and science learning outcomes tests. Data analysis techniques included descriptive analysis to see the level of anxiety and scientific literacy abilities as well as inferential analysis to test research hypotheses. Based on the results of data analysis in the first hypothesis, it shows a sig. (0.676) > Î± (0.05), then H0 is accepted, which means that there is no relationship between anxiety about studying physics and students' science learning outcomes. In the second hypothesis, the sig value. (0.002) < Î± (0.05), then H0 is rejected, which means that there is a relationship between scientific literacy abilities and students' science learning outcomes. Furthermore, the third hypothesis shows a significance value of 0.571 and 0.779 > Î± (0.05) so it can be concluded that there is a linear relationship between learning anxiety and student learning outcomes and scientific literacy abilities and science learning outcomes of PGSD students.